A influência da mucosa queratinizada ao redor de implantes no desconforto à escovação e na saúde peri-implantar - Souza, André Barbisan de (2014)
The aim of thisstudy was to compare the degree of brushing discomfort (BD) and peri-implant soft tissues health in patients presenting implant sites with ≥ 2 mm or < 2 mm of keratinized mucosa (KM). The patients were recruited during their return for maintenance therapy from January to October, 2013. Based on the presence of KM, the patients were divided into 2 groups: presence of implant sites with ≥ 2 mm of KM (Group A) and presence of implant sites with < 2 mm of KM (Group B). At the beginning of the experiment, clinical measurements of plaque index (PI), probing pocket depth (PPD), clinical atachment level (CAL) and bleeding on probing (BoP) were performed in 3 sites/implant (buccal aspect). Immediately after oral hygiene instructions, the patients were asked to perform brushing of the experimental implant sites. Subsequently, the patients reported on the corresponding brushing discomfort using the Visual Analog Scale (VAS). Non-paired student-t test and Mann-Whitney test were performed to analyze the outcome variables. Level of significance was established in 5%. Seventy-nine patients with a total of 269 implant sites were included. The results showed that the implant sites in Group B exhibited more BD (p<0.001), PI (p=0.0021) and BoP (p=0.017) than the implant sites from Group A. It was demonstrated that implant sites with < 2 mm of KM were more prone to brushing discomfort, plaque accumulation and peri-implant inflammation.